Strong angular dependent transmission ratio due to interplay between spin waves and the domain wall in perpendicular magnetic anisotropy materials - Chang, Liang-Juan; Liu, Yen-Fu; Kao, Ming-Yi; Tsai, Li-Zai; Liang, Jun-Zhi; Lee, Shang-Fan (2017)
Spin waves (SW) can induce rich domain wall (DW) motion in a perpendicular-magnetic anisotropy nanostrip. In-plane magnetization tilt angle resulting from the fluctuation of the effective field of the magnetization response in the DW region plays an essential role in the dynamics of SW interacting with a DW. We performed simulation and found that the transmission ratio of the propagating SW across the DW depends strongly on the tilt angle in the low-frequency regime. The material parameters and the geometrical configuration can be fine-tuned for practical devices.